Improved control of septoria tritici blotch in durum wheat using cultivar mixtures. (23rd August 2020) - Ben M'Barek, Sarrah; Karisto, Petteri; Abdedayem, Wided; Laribi, Marwa; Fakhfakh, Moez; Kouki, Hajer; Mikaberidze, Alexey; Yahyaoui, Amor
Abstract: Mixtures of cultivars with contrasting levels of resistance can suppress infectious diseases in wheat, as demonstrated in numerous field experiments. Most studies focus on airborne pathogens in bread wheat, while splash‐dispersed pathogens have received less attention, and no studies have been conducted in durum wheat. We conducted a 2‐year field experiment in Tunisia to evaluate the performance of cultivar mixtures with varying proportions of resistance (0%–100%) in controlling the polycyclic, splash‐dispersed disease septoria tritici blotch (STB) in durum wheat. To measure STB severity, we used a high‐throughput method based on digital image analysis of 3, 074 infected leaves collected from 42 and 40 experimental plots during the first and second years, respectively. This allowed us to quantify pathogen reproduction on wheat leaves and to acquire a large data set that exceeds previous studies with respect to accuracy and precision. Our analyses show that introducing only 25% of a disease‐resistant cultivar into a pure stand of a susceptible cultivar provides a substantial reduction of almost 50% in disease severity compared to the susceptible pure stand. However, incorporating two resistant cultivars instead of one did not further improve disease control, contrary to predictions of epidemiological theory. Susceptible cultivars can be agronomically superior to resistant cultivars or be better accepted by growers for other reasons. Hence, if mixtures with only a moderate proportion of the resistant cultivar provide a similar degree of disease control as resistant pure stands, as our analysis indicates, such mixtures are more likely to be accepted by growers. Abstract : In durum wheat, strong protection against septoria tritici blotch is achieved by using a cultivar mixture that contains only 25% of a resistant cultivar together with a susceptible one.